Influence of Solvents' Polarity on the Physicochemical Properties and Photocatalytic Activity of Titania Synthesized Using Deinbollia pinnata Leaves - Rufai, Yakubu; Chandren, Sheela; Basar, Norazah (Frontiers in Chemistry, 2020)
Nanotechnology is one of the most interesting areas of research due to its flexibility to improve or form new products from nanoparticles (NPs), and as a fast, greener, more eco-friendly and sustainable solution to technological and environmental challenges. Among metal oxides of photocatalytic performance, the use of titania (TiO2) as photocatalyst is most popular due to its unique optical and electronic properties. Despite the wide utilization, the synthesis of TiO2 NPs bears many disadvantages: it utilizes various less environmental-friendly chemicals, high cost, requires high pressure and energy, and potentially hazardous physical and chemical methods. Hence, the development of green synthesis approach with eco-friendly natural products can be used to overcome these adverse effects. In this work, TiO2 NPs have been prepared by using Deinbollia pinnata leaves extracts, obtained by different solvents (n-hexane, ethyl acetate and ethanol) with different polarities. The extracts acted as the reducing agent, while titanium isopropoxide as the precursor and water as the solvent. X-ray diffraction (XRD) pattern confirmed the synthesized TiO2 consist of anatase phase in high purity, with average crystallite size in the range of 19 – 21 nm. Characterization by using field emission scanning electron microscopy (FESEM) showed the TiO2 NPs possess a uniform semi-spherical shape in the size range of 33 – 48 nm. The energy dispersive X-ray (EDX) spectra of green TiO2 NPs showed two peaks for the main elements of Ti (61 Wt.%) and O (35 Wt.%). The band-gap energy of 3.2 eV was determined using UV-Vis spectroscopy. From the nitrogen sorption analysis, type V isotherm of the material was obtained, with BET surface area of 31.77 m2/g. The photocatalytic activity of synthesized TiO2 was evaluated for photodegradation of methyl orange (MO) under UV light irradiation. Based on the results, it is shown that TiO2 NPs synthesized with D. pinnata leaves extracted using ethyl acetate showed the most effective photodegradation performance, achieving 98.7% of MO conversion within 150 mins. It can be concluded that the use of plant extracts in synthesis with TiO2 managed to produce highly crystalline anatase TiO2 with superior photocatalytic activity in the photodegradation of organic dye.